KORESIA: DEVELOPMENT AND VALIDATION OF AN INTEGRATED DIGITAL LEARNING PLATFORM FOR CORRESPONDENCE IN OFFICE ADMINISTRATION EDUCATION - Eka Dewi Utari; Maulana Amirul Adha; Mayang Riyantie; Ferry Setyadi Atmadja; Bayu Suhendry; Inqy Azzahra Putri (Universitas Negeri Surabaya, 2026)
Phenomenon/Issue: Vocational high school (SMK) graduates in Indonesia continue to record the highest open unemployment rate among all education levels, reaching 9.01% in August 2024 against a national average of 4.91%, a gap consistent with long standing concerns about vocational skills instruction quality, including correspondence competencies in Office Administration Education, where digital learning media remain fragmented across separate platforms for materials, practice, and evaluation. Purpose: This study developed and validated KORESIA, an integrated digital correspondence learning media, and examined its practicality among vocational high school students Novelty: KORESIA integrates materials, instructional video, structured procedural practice for letter typing, letter folding, and telephone handling, and automated evaluation within a single platform, evaluated through a staged mechanism combining expert validation with progressively broader user testing. Research Methods: Using a Research and Development approach guided by the ADDIE model, the product was validated by two media experts and two content experts on a 1-5 Likert instrument, then tested through a one-to-one trial (three students per school) and a small group trial (six to seven students per school) at SMKN 62 Jakarta and SMKN 40 Jakarta. Results: Media validation scores ranged from 76.25% to 81.33% (Feasible to Highly Feasible), content validation scores ranged from 96.67% to 100% (Highly Feasible), and practicality scores across both trial stages and schools averaged 92.31% (Highly Practical). Research Contributions: This study offers an empirically validated model for integrated digital correspondence learning media and practical guidance for developing similarly integrated media for other procedurally demanding vocational competencies.